Effects of Nishyinda, black pepper and cinnamon extract as growth promoter in broilers - Molla, MR; Rahman, MM; Akter, F; Mostofa, M (Bangladesh Veterinarian, 2013)
An extract of nishyinda (Vitex negundo) leaves, black pepper (Piper nigrum) and cinnamon (Cinnamomum verum) (polyherbal extract) were used as growth promoter in broilers. A total of 20 day-old broiler chicks were purchased and after seven days of acclimatization randomly divided into two equal groups. No vaccination schedule was practised and no antibiotics were added in rations. Group A served as control while group B was supplemented with polyherbal extract 1 mL/litre in drinking water. Weekly body weight gain up to six weeks was measured and blood tests were performed at 21 and 42 days. Polyherbal extract significantly (P<0.05) improved weight gain. There was no change in haematological parameters. It can be concluded that the polyherbal extract was safe as a growth promoter in broiler production without adverse effects on chicken health. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14345 Bangl. vet. 2012. Vol. 29, No. 2, 69-77